2008
DOI: 10.1063/1.2908960
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of thermal and fatigue behavior in K0.5Na0.5NbO3-based lead free piezoceramics

Abstract: K 0.5 Na 0.5 NbO 3 -͑KNN͒ based lead free materials have been found to exhibit good piezoelectric properties ͑d 33 ϳ 250 pC/ N͒ due to the orthorhombic-tetragonal polymorphic phase transition ͑PPT͒ temperature compositionally shifted downward to near room temperature. However, associated with the PPT are issues of temperature and domain instability, making them impractical for applications. In this work, CaTiO 3 ͑CT͒ was used to effectively shift the PPT downward in effort to mitigate these issues. As expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
111
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 25 publications
1
111
1
Order By: Relevance
“…[3][4][5] Since Saito et al 6 have demonstrated that the KNN ceramics modified with Li, Ta, or Sb exhibit sufficient piezoelectric properties comparable to commercially available PZT-based ceramics, considerable interests have been devoted to improve the piezoelectric properties of KNN ceramics. [7][8][9][10][11] Doping is a mandatory solution to tailor the properties of KNN for specific applications. For Mn-doped KNN and KNN based ceramics, the improved electrical properties were observed.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Since Saito et al 6 have demonstrated that the KNN ceramics modified with Li, Ta, or Sb exhibit sufficient piezoelectric properties comparable to commercially available PZT-based ceramics, considerable interests have been devoted to improve the piezoelectric properties of KNN ceramics. [7][8][9][10][11] Doping is a mandatory solution to tailor the properties of KNN for specific applications. For Mn-doped KNN and KNN based ceramics, the improved electrical properties were observed.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Therefore, it is necessary to carefully investigate the fatigue characteristics of promising lead-free compositions. Especially, only a few fatigue studies have been published so far for KNN-based materials, [20][21][22][23] and a detailed understanding of the unipolar fatigue mechanism, which is crucial for further improving the unipolar fatigue resistance, is still missing.…”
mentioning
confidence: 99%
“…Recently, potassium sodium niobate (KNN)-based ceramics are expected to have excellent piezoelectric, [9][10][11][12][13][14][15][16][17] ferroelectric and dielectric properties near orthorhombic-tetragonal polymorphic phase transition (PPT) temperature. [18][19][20] Saito et al have reported Li, Ta, Sb doped KNN ceramics with high piezoelectric constant of 416 pC/N by templated grain growth (TGG) method. 9 When Na/K ratio is near 0.5/0.5, KNN system possesses a PPT similar to that of PZT system.…”
Section: Introductionmentioning
confidence: 99%
“…It will lead to the distortion of structure and make it shifts to PPT region at room temperature. [18][19][20] In Li, Sb and Ta co-doped KNN ceramics, the introduction a To whom correspondence should be addressed. : +86-10-62517887; Tel: +86-10-82501673.…”
Section: Introductionmentioning
confidence: 99%